2008
DOI: 10.1007/s10165-008-0120-6
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus and dermatomyositis with symptomatic bilateral sacroiliitis: an unusual and interesting association

Abstract: Systemic lupus erythematosus (SLE) is a multisystem autoimmune connective-tissue disease with a complex phenotype and varying disease course. Although SLE often causes a polyarticular synovitis, there are only a few case reports of abnormalities of the synovial lined sacroiliac joints. We report a case with an overlap syndrome of SLE and dermatomyositis who subsequently developed bilateral symptomatic sacroiliitis. We conclude that sacroiliitis, although rare, can occur in patients with active SLE as a manifes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Interestingly, most of the reported patients with the coexistence of SLE and AS, including the present case, are female (F/M: 6/3). In most cases, including the present case, SLE symptoms preceded those of AS (F/M: 5/4) (4,5,6,9). On the other hand, the association between HLA-B27 and AS is well known, and the HLA-B27 molecule plays a role in the pathogenesis of AS.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Interestingly, most of the reported patients with the coexistence of SLE and AS, including the present case, are female (F/M: 6/3). In most cases, including the present case, SLE symptoms preceded those of AS (F/M: 5/4) (4,5,6,9). On the other hand, the association between HLA-B27 and AS is well known, and the HLA-B27 molecule plays a role in the pathogenesis of AS.…”
Section: Discussionsupporting
confidence: 46%
“…These two autoimmune rheumatologic diseases, which have a different aetiopathogenesis as well as diverse clinical and genetic characteristics, are rarely seen together. To the best of our knowledge, there are only 8 reported cases of the coexistence of SLE and AS in the English literature (3)(4)(5)(6)(7)(8)(9)(10). Here, we report another case with the coexistence of these two diseases.…”
Section: Introductionmentioning
confidence: 76%
“…Systemic lupus erythematosus (SLE) belongs to a family of related autoimmune rheumatic disorders, including dermatomyositis, scleroderma, polymyositis, mixed connective tissue disease, and rheumatoid arthritis. All of these disorders are capable of affecting multiple organs, and the symptoms in systemic rheumatic diseases often overlap as has been repeatedly reported in the literature [1][2][3][4][5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…and is about the association of spondyloarthropathies and lupoid syndromes. Several case reports and studies, focusing on sacroiliitis in systemic lupus erythematosus (SLE) and other connective tissue diseases, have suggested that sacroiliac involvement could be a part of the clinical course . When we look at SSc, description of this rare association is demonstrated first in 1847 and cited by Benedek and Rodnan in 1982 .…”
Section: Introductionmentioning
confidence: 99%